The impact of the increasing world food prices on the agricultural trade sector of the Sudan - Elgali, Mohamed; Mustafa, Rajaa; Kirschke, D. (Gezira Journal of Agricultural Science; Vol 9 No 2 (2011), 2011)
The objective of this study was to assess the responses of economic variables (supply and demand) to the world high prices and their consequences on the agricultural trade of Sudan, in addition to estimate the impact of liberalization policies. In this study a multi-market, partial equilibrium model is used as a main tool to assess policy and the price impact on the agricultural crop markets of the Sudan. Partial equilibrium models are the most widely used models to assess the effect of various policy interventions on agricultural sector. The high world prices has a positive impact on the agricultural markets supplies. This improvement is reflected in the growth of local supplies of the import substitutes of wheat and rice. With regard to the demand for agricultural goods, rising prices incapacitate consumers access to staple food that is reflected by the noticeable decrease in the quantity demanded for most of the agricultural goods especially the imported and locally produced cereals. Regarding the impact on trade, agricultural crop markets are showing improvement under the high prices scenario; evident by the increase in export growth rate of 335.9%. Following the recommendations of the World Bank to lower domestic prices through reducing tariffs and other taxes on key staples, the liberalization scenarios are introduced to the model. Under these scenarios, market supplies would show positive responses at lower rates. The demand of major cereals will fall at lower levels than that with the existence of taxes.    تهدف هذه الدراسة إلى تقييم استجابة المتغيرات الاقتصادية الزراعية للأسعار العالمية المرتفعة في العالم وأثارها على التجارة الزراعية الخارجية بالإضافة إلى تقدير أثر سياسات التحرير الاقتصادي. في هذه الورقة تم استخدام نموذج الأسواق المتعددة والتوازن الجزئي كأداة رئيسة للتحليل وتحليل اثر الأسعار على أسواق المحاصيل الزراعية في السودان، حيث تعتبر نماذج التوازن الجزئية من أكثر أنواع النماذج انتشاراً في استعمالها لتقويم اثأر السياسات في قطاع الزراعة .أوضحت النتائج إن الأسعار العالمية لديها اثر ايجابي على عرض السلع الزراعية وهذا التطور  ينعكس في زيادة عرض السلع المحلية والسلع الاحلاليه المستوردة على حد سواء. أوضحت النتائج انه بالنسبة للطلب على السلع الزراعية فان الأسعار العالمية المتزايدة قد حدت من إتاحة الطلب عليها وذلك يتضح جلياً في نقص الطلب على معظم السلع الزراعية المنتجة محلياً. أما من ناحية التجارة الخارجية فان الأسعار المرتفعة أدت إلى تطور كبير فيها . وبإتباع توصيات البنك الدولي بتطبيق سياسات تعمل على تخفيض الأسعار المحلية وذلك من خلال تخفيض التعرفه الجمركية و الضرائب فان سيناريوهات سياسة التعرفة طبقت على النموذج حيث أوضحت النتائج إن عرض السلع الزراعية ما زال مرتفعاً وان الطلب على سلع الحبوب سينخفض إلي مستويات اقل مما كانت عليه.